Accounting issues in Calculating Taxes on Corporate Entities revenue of Entrepreneurs in Luang Prabang Municipality, Luang Prabang Province: https://doi.org/10.69692/SUJMRD0802117 - PHENGSAVAT, Sitthivikone; JIRAHDETPRAPAI DR, Nanthaphan; SOMSACKXAYSOMPHENG, Oulavieng; NORCHANDA, Sithone; SOUADA , Souaxiong; SENGCHANH, Vilaxai (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
In this study, the research team studied the accounting issues in calculating tax on corporate entities’ revenue of entrepreneurs in Luang Prabang Municipality, Luang Prabang Province. The purposes are to study the level of accounting problems in calculating the corporate income tax of entrepreneurs. To compare the level of accounting problems in calculating the corporate income tax of entrepreneurs by individual factors, the population used in the research was the accounting staff or entrepreneurs who calculated the corporate income tax of the business entities registered with the enterprises, a simple number of randoms 254 totally. The statistics used in the data analysis included descriptive and parameter reference statistics with the following values: frequency, percentage, mean, standard deviation, one-way ANOVA test, and paired test by LSD method. The results of the research were as follows: 1) The level of accounting problems in calculating the corporate income tax of business entities is as follows: Overall, it is at a moderate level which analyzed each aspect is sorted from large to small: the calculation of the depreciation of property prices in several levels, the improvement of accounting expenses tax is at a moderate level and the improvement of accounting income to a tax at a moderate level. ( 2 ) Comparison of the level of accounting problems in calculating the corporate income tax of entrepreneurs by classification according to personal factors such as classified by level of education found entrepreneurs there are different levels of education in accounting problems in calculating the corporate income tax varies two aspects are to improve the accounting expenses to be tax and to improve the accounting income to be tax and to classify according to the work experience of the entrepreneur found entrepreneurs with different work experience there are accounting problems in calculating the corporate income tax varies two aspects are the adjustment of accounting expenses to tax and the calculation of the depreciation of property prices.